Cardiovascular effects of stimulant and non-stimulant medication for children and adolescents with ADHD: a systematic review and meta-analysis of trials of methylphenidate, amphetamines and atomoxetine - Hennissen, Leonie; Banaschewski, Tobias; Dittmann, Ralf (CNS drugs, 2017)
Background: Many children and adolescents with attention deficit/hyperactivity disorder (ADHD) are treated with stimulant and non-stimulant medication. ADHD medication may be associated with cardiovascular effects. It is important to identify whether mean group effects translate into clinically relevant increases for some individual patients, and/or increase the risk for serious cardiovascular adverse events such as stroke or sudden death. Objectives: To evaluate potential cardiovascular effects of these treatments, we conducted a systematic review and meta-analysis of the effects of methylphenidate (MPH), amphetamines (AMP), and atomoxetine (ATX) on diastolic and systolic blood pressure (DBP, SBP) and heart rate (HR) in children and adolescents with ADHD. Methods: We conducted systematic searches in electronic databases (PsychINFO, EMBASE and Medline) to identify published trials which involved individuals who were (i) diagnosed with ADHD and were aged between 0-18 years; (ii) treated with MPH, AMP or ATX and (iii) had their DBP and SBP and/or HR measured at baseline (pre) and the endpoint (post) of the study treatment. Studies with an open-label design or a double-blind randomised control design of any duration were included. Statistical analysis involved calculating differences between pre- and post-treatment measurements for the various cardiovascular parameters divided by the pooled standard deviation. Further, we assessed the percentage of clinically relevant increased BP or HR, or documented arrhythmias. Results: Eighteen clinical trials met the inclusion criteria (10 for MPH, 5 for AMP, and 7 for ATX) with data from 5837 participants (80.7% boys) and average duration of 28.7 weeks (range 4-96 weeks). All three medications were associated with a small, but statistically significant pre-post increase of SBP (MPH: standard mean difference [SMD] 0.25, 95% confidence interval [CI] 0.08-0.42, p < 0.01; AMP: SMD 0.09, 95% CI 0.03-0.15, p < 0.01; ATX: SMD 0.16, 95% CI 0.04-0.27, p = 0.01). MPH did not have a pre-post effect on DBP and HR. AMP treatment was associated with a small but statistically significant pre-post increase of DBP (SMD 0.16, CI 0.03-0.29, p = 0.02), as was ATX treatment (SMD 0.22, CI 0.10-0.34, p < 0.01). AMP and ATX were associated with a small to medium statistically significant pre-post increase of HR (AMP: SMD 0.37, CI 0.13-0.60, p < 0.01; ATX: SMD 0.43, CI 0.26-0.60, p < 0.01). The head-to-head comparison of the three medications did not reveal significant differences. Sensitivity analyses revealed that AMP studies of <18 weeks reported higher effect sizes on DBP compared with longer duration studies (F(1) = 19.55, p = 0.05). Further, MPH studies published before 2007 reported higher effect sizes on SBP than studies after 2007 (F(1) = 5.346, p = 0.05). There was no effect of the following moderators: type of medication, doses, sample size, age, gender, type of ADHD, comorbidity or dropout rate. Participants on medication reported 737 (12.6%) other cardiovascular effects. Notably, 2% of patients discontinued their medication treatment due to any cardiovascular effect. However, in the majority of patients, the cardiovascular effects resolved spontaneously, medication doses were changed or the effects were not considered clinically relevant. There were no statistically significant differences between the medication treatments in terms of the severity of cardiovascular effects. Conclusions: Statistically significant pre-post increases of SBP, DBP and HR were associated with AMP and ATX treatment in children and adolescents with ADHD, while MPH treatment had a statistically significant effect only on SBP in these patients. These increases may be clinically significant for a significant minority of individuals that experience larger increases. Since increased BP and HR in general are considered risk factors for cardiovascular morbidity and mortality during adult life, paediatric patients using ADHD medication should be monitored closely and regularly for HR and BP.
Gesehen am 12.04.2018